1999
DOI: 10.21273/hortsci.34.3.442f
|View full text |Cite
|
Sign up to set email alerts
|

012 Inhibition of Phytophthora megasperma in Coconut Coir-based Root Substrates

Abstract: Glycine max (soybean) seed were sown in root substrates composed of 80:0:20 or 0:80:20 coconut coir dust (coir):Sphagnum peat (peat):perlite (v/v) amended with dolomitic limestone to a pH of 5.5. Substrates were inoculated with Phytophthora megasperma races 5 and 25 isolated from soybean and grown in dilute liquid V-8 cultures. Uninoculated controls were included. Containers were watered daily to maintain moisture levels at or near container capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Our study complements the study of Candole and Evans (2004) by demonstrating in vitro that coir can suppress soilborne plant pathogens and that this suppression is largely due to microorganisms associated with the substrate.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Our study complements the study of Candole and Evans (2004) by demonstrating in vitro that coir can suppress soilborne plant pathogens and that this suppression is largely due to microorganisms associated with the substrate.…”
Section: Discussionsupporting
confidence: 62%
“…w Fisher's least significant difference at P = 0.05. reticulisporum, and several Penicillium species (Waller et al, 2008). Candole and Evans (2004) demonstrated that when tomato seedlings were grown in coir, the incidence of damping off was reduced by 88%, 90%, and 41% for P. capsici, P. nicotianae, and P. aphanidermatum, respectively, compared with peat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations